The Bidirectional Position control of the Prismatic joint for Motorized single link Robotic arm using Adaptive Super-Twisting Sliding Mode Control - G., Then Mozhi; M., Banu Sundareswari; K., Dhanalakshmi (PREPARE@u® | IEI Conferences, 2021)
Dual layer adaptive super-twisting sliding mode control strategy (ASTSMC) designed for the position control of motor coupled flexible robotic arm is presented in this article. The system is modeled using the constraints computed for the DC motor using the nonlinear least-square (NLS) parameter estimation method. The flexible manipulator is modeled using lumped parameter model approach and the fixed extremity of the flexure is positioned at the desired point by the DC motor and the lead-screw linear actuation system. The super twisting algorithm and adaptive law is employed to control the system and the results are compared with PID controller and classical SMC. The final position accuracy is ensured, and the positioning performance is enhanced by ASTSMC controller design, and the simulated and experimental results show that the design of the proposed integrated mechanism and control system based on ASTSMC is effective in achieving precision in the placement of the flexure.